Axial rotation affects the cognitive characteristics of spatial ability - Feng, Tian; Zhang, Fuchun; Liu, Jinzhao; Liang, Manqi; Li, Yawei (Frontiers in Psychology, 2024)
Purpose: To test spatial ability in athletes with different axial rotation experience and analyze their behavioral data to explain the cognitive mechanisms of spatial ability in athletes. Methods: Experiment 1: A total of 147 athletes were selected for the paper-and-pencil mental rotation test (MRT). The athletes were separated according to three sport types: open high-spatial (OH) sport, closed high-spatial (CH) sport, closed low-spatial (CL) sport. Spatial ability testing with a two-factor mixed experimental design of 3 (sport type) × 2 (stimulus type). Experiment 2: In this study, 47 players were selected for computerized mental rotation test, with a three-factor mixed experimental design of 3 (sport type) × 2 (angle: 45°, 90°) × 3 (rotational axis: left-right axis, up-down axis, and front-back axis). Repeated-measures ANOVA was performed to evaluate the data. Results: (1) the CH group and OH group outperformed the CL group in the non-embodied task (all ps<0.003) and the CH group was better than the other groups in the embodied and tasks (all ps <0.008). (2) Under 45° rotational conditions, the reaction time (RT) for the left-right (LR) and up-down (UD) axes were shorter than that for the front-back (FB) axis (all ps <0.026). However, under 90° conditions, the RT for FB